2022
DOI: 10.37058/jelita.v1i2.4761
|View full text |Cite
|
Sign up to set email alerts
|

Demotivated Students during Online English Learning in Covid-19 Pandemic: Voices from Indonesian Students

Abstract: The COVID-19 pandemic has forced all sectors to stop their activities. As a result of this, learning activities were suddenly changed to online methods. Seeing the phenomena that occur around researchers, the decreasing of students' motivation during online English learning can be a serious matter. If the demotivating factor cannot be known, it will be difficult for the teacher to overcome it. To fill this gap, the researcher intends to look for the factors that cause demotivation in students during online Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…Previous studies showed that demotivation of learning online can be the result of internal and external factors. These factors could cause dissatisfaction within and outside an individual towards online learning (Pratama et al, 2022). According to Che Soh et al (2022), before the trigger of demotivation developed an internal process, it began with an external locus.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Previous studies showed that demotivation of learning online can be the result of internal and external factors. These factors could cause dissatisfaction within and outside an individual towards online learning (Pratama et al, 2022). According to Che Soh et al (2022), before the trigger of demotivation developed an internal process, it began with an external locus.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Sumarsono et al (2022), en la misma línea que el resto de trabajos, certifi caron menos interacción entre estudiantes y profesorado, enseñanzas menos efectivas y errores de conexión como principales factores desmotivadores. Otras investigaciones como la de Nabila et al (2021), Pratama et al (2022) o Liu (2022) son consistentes con las anteriores porque mencionan factores como la falta de interacción, más deberes, Internet lento o problemas de conexión, falta de apoyo de padres, demasiado tiempo de pantalla e infl uencia negativa de los compañeros.…”
Section: La Desmotivación En El Aprendizaje De Idiomas Durante El Cov...unclassified
“…Los ítems 17, 4 y 36 se refi eren a la cantidad de tareas propuestas, a si los estudiantes se sienten o no con vergüenza a la hora de hablar y a si Zoom es una plataforma adecuada. Esto es consistente con otras investigaciones: Nabila et al (2021), Pratama et al (2022) o Liu (2022. Es decir, hay una falta de adecuación de la enseñanza a las nuevas circunstancias.…”
Section: Prueba De Kmo Y Bartlettunclassified
“…They use modular learning; however, they provide feedback through different social media platforms and/or messaging. The problem lies with the fact that not all learners have gadgets, a stable internet connection, and a budget for learning (Dewi, et al, 2022;Santiana, et al, 2021;Pratama & Dewi, 2022). Thus, it's challenging for teachers to provide learners with feedback.…”
Section: Introductionmentioning
confidence: 99%